Echocardiographic findings following renal sympathetic denervation for treatment resistant hypertension, the ReShape CV-risk study - Anna Subbotina; Eystein Skjølsvik; Marit Dahl Solbu; Atena Miroslawska; Terje Steigen (Blood Pressure)
Objective The aim of this study was to describe and compare echocardiographic findings before renal sympathetic denervation (RDN) and 6 and 24 months after the procedure.Materials and methods Patients with treatment resistant hypertension (TRH) were included in this non-randomised intervention study. RDN was performed by a single experienced operator using the Symplicity Catheter System. Echocardiographic measurements were performed at baseline, and after 6 and 24 months.Results The cohort consisted of 21 patients with TRH, with a mean systolic office blood pressure (BP) of 163 mmHg and mean diastolic BP 109 mmHg. Mixed model analysis showed no significant change in left ventricular (LV) mass index (LVMI) or left atrium volume index (LAVI) after the RDN procedure. Higher LVMI at baseline was significantly associated with greater reduction in LVMI (p < 0.001). Relative wall thickness (RWT) increased over time (0.48 mm after two years) regardless of change in BP. There was a small but significant reduction in LV end-diastolic (LVIDd) and end-systolic (LVIDs) diameters after RDN, with a mean reduction of 2.6 and 2.4 mm, respectively, after two years. Progression to concentric hypertrophy was observed only in in patients who did not achieve normal BP values, despite BP reduction after RDN.Conclusion There was no reduction of LV mass after RDN. We found a small statistically significant reduction in LVIDd and LVIDs, which together with increase in RWT can indicate progression towards concentric hypertrophy. BP reduction after RDN on its own does not reverse concentric remodelling if target BP is not achieved.